Preparation of functional currant-bun-like fumed silica/polymethacrylate nanoparticles by radiation-induced polymerization - Martínez, Leandro Julián (2014)
Fumed silica (FS) is one of the few nanomaterials used in large scale in the production of several industrial products. In addition, the very low toxicity of these nano-sized particles led them to become excellent raw materials to develop novel applications in the field of downstream processing of bioproducts. In this work, we prepared and characterized a colloidal composite based on fumed silica with protein adsorption properties. This nanocomposite was prepared by radiation-induced polymerization of glycidyl methacrylate (GMA) dissolved in an aqueous suspension of FS without stirring. According to the initial GMA/FS ratio, mono-disperse nanoparticles from 60 to 195 nm were obtained. Sulfonic nanoparticles allowed reversible lysozyme adsorption up to 270 mg/g. The nanomaterials prepared have potential application as protein-capture materials in the field of downstream processing of proteins.